I never promised you a rose garden - Greenberg, Joanne; Green, Hannah (New York, New York The New American Library, 1964)
Chronicles the three-year battle of a mentally ill, but perceptive, teenage girl against a world of her own creation, emphasizing her relationship with the doctor who gave her the ammunition of self- understanding with which to destroy that world of fantasy.
" A Signet book."
Photocopy.
Originally published: Holt, Rinehart and Winston, c1964.
Keywords: Mental ill -- Fiction; Mental illness -- Fiction